The transfer of HRM policies and practices in American multinational hotels in Saudi Arabia - Al-Khaldi, Amal Hatem (Curtin University, 2016)
Competitive pressures have increased the focus of HRM in MNEs and HRM transfer processes across borders. Consequently, this study examines the transfer of HRM policies and practices in US MNEs and their subsidiaries based in Saudi Arabia. In particular, the aim of the study is to determine the extent to which US MNEs transfer HRM policies and practices from their Headquarters to their subsidiaries and to identify the factors that facilitate and inhibit HRM transfer.